Philippine National Police Initiatives in the Promotion of Peace and Order in Iligan City: Basis for Policy Recommendation - Galabin, Noel D.; Pallega, Rowell B.; Recapente, Marvin A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
This study aimed to determine the extent of the Philippine National Police Operation initiatives in the promotion of peace and order in Iligan City as a basis for policy recommendation. This study made use of a non-experimental quantitative research design utilizing the descriptive correlational technique, frequency count, percentage, mean and standard deviation, paired t-test, and Pearson-r correlations. The respondents exhibited a high level of response that the Philippine National Police always performed the police operational procedure initiatives in the promotion of peace and order. The finding showed that overall, there was a significant relationship between the frequency of implementation of police operations and the crime rate in terms of Index and non-index crime. Further studies are warranted.